Factors Affecting the Preparation of Financial Statements based on FAS MSME - Nurapni Jami Putri; Zesmi Kusmila (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine what factors influence the preparation of financial statements based on FAS MSME on Micro, Small, and Medium Enterprises activities in Sungai Full City. The type of research used is quantitative research. The population in this study is MSME actors, and sampling techniques used random sampling. Data collection is carried out by distributing questionnaires, where respondents answer questions that have been provided answers. The results of this study show that the dominant influencing factors in the preparation of financial statements based on FAS MSME are knowledge of accounting standards and cost perception. With a good understanding of accounting standards, MSMEs can optimize financial performance, gain access to sources of financing, make the right business decisions, increase transparency, and invest in the quality of financial statements